HPV infekce a cervikální intraepiteliální neoplázie - Sevcík, L; Koliba, P; Konderla, M; Gráf, P; Hlavacka, J (Ceska gynekologie, 2003)
OBJECTIVE: To determine the presence of high-risk, oncogenic types of HPV infection (HR HPV) and the presence of HPV 16 and 18 in various degrees of cervical and intraepithelial neoplasia. TYPE OF THE STUDY: A retrospective study. NAME AND ADDRESS OF THE INSTITUTION: Obstetrical-Gynecological Clinic, Faculty Hospital, Ostrava. METHODS: The study included 205 female patients indicated for conization due to cervical intraepithelial neoplasia. The conization was preceded by extended colposcopy, cytological samplings, HPV DNA test and a directed biopsy. HR HPV was examined in all patients, HPV 18 and 16, respectively, in 98 (48%) patients. Based on severity of histopathological findings the patients were divided into three groups, examined for positivity of oncogenic HPV types and the high risk HPV 18 and HPV 18 types, respectively. RESULTS: The histopathological findings from a total number of 205 conuses included five (2%) benign lesions, 85 (41%) CIN1, 77 (38%) CIN 2 and 38 (19%) CIN 3. Altogether the HR HPV was demonstrated in 143 (70%) patients. In patients with the benign lesion no HPV infection was detected. In patients with the CIN 1 finding the HR HPV infection was detected in 35 (41%) cases, in patients with CIN 2 in 70 (91%) cases and in patients with CIN 3 in 38 (100%) cases. HPV 16 was diagnosed in patients with the CIN 1 finding in 9 (23%) cases, HPV 16 in 5 (6%) cases and both types of the virus were present in two (2%) cases. In CIN 2, HPV 16 was positive in 17 (43%) and HPV 18 in 6 (8%) cases. In patients with CIN 3, HPV 18 was detected in 9 (53%) and HPV 18 in 2 (5%) patients. In all the women who underwent conization, HPV 16 infection was demonstrated in 17% and HPV 18 in 6% patients. In 19% of patients, the infection by at least one type of the virus was present and in two % both types of the virus were present. CONCLUSION: The presence of HR HPV rises with increasing severity of cervical intraepithelial neoplasia, HR HPV being detected in all cases suffering from CIN 3. The highest risk type HPV 16 was present with increasing rate in relation to the severity of cervical intraepithelial neoplasia, whereas no such trend was present in case of HPV 18.
Keywords: Humans; lidé středního věku; Tumor Virus Infections; Female; Aged; dospělí; nádory děložního čípku; senioři; lidé; Papillomaviridae; Adult; Papillomavirus Infections; ženské pohlaví; Middle Aged; dysplazie děložního hrdla; infekce papilomavirem; Uterine Cervical Neoplasms; Uterine Cervical Dysplasia; infekce onkogenními viry